The Chinafication of Hollywood: Chinese consumption and the self-censorship of U.S. films through a case study of Transformers Age of Extinction - Lukinbeal, Chris (ERDKUNDE, 2019)
For Hollywood films, the international box office is now financially more important than the domestic market. China will soon become the world’s largest box office for Hollywood films. To gain access to the Chinese market foreign films must be approved by China’s government. Movies must not disparage Chinese culture, landmarks, or the government. Eager to comply, Hollywood producers are not waiting until they are reviewed to make changes and instead are self-censoring in advance rather than risk being denied access. In this paper, I use a representation-in-relation-to approach to cultural geography that positions a film’s text in relation to its production practices to understand the way Hollywood is remaking itself to appeal to China. The representation-in-relation-to approach takes practice seriously without jettisoning the power of representation. I apply this approach to Transformers: Age of Extinction, which through its production practices provides a case study on what trade publications are referring to as the ‘Chinafication of Hollywood.’ In an industry driven by profit, the Chinafication of Hollywood is a form of influence that further limits the creativity and uniqueness of Hollywood movies by prescribing what gets made and how it is represented. Transformers: Age of Extinction is an important cultural text, not for its narrative content, but for how its representation relates to the production practices that allowed it to become China’s largest grossing film at that time and the only billion-dollar blockbuster of 2014.